Transformation pathways and acute toxicity variation of 4-hydroxyl benzophenone in chlorination disinfection process. (July 2016) - Liu, Wei; Wei, Dongbin; Liu, Qi; Du, Yuguo
Abstract: Benzophenones compounds (BPs) are widely used as UV filters, and have been frequently found in multiple environmental matrices. The residual of BPs in water would cause potential threats on ecological safety and human health. Chlorination disinfection is necessary in water treatment process, in which many chemicals remained in water would react with disinfectant chlorine and form toxic by-products. By using ultra performance liquid phase chromatography quadrupole time of flight mass spectrometer (UPLC-QTOF-MS), nuclear magnetic resonance (NMR), the transformation of 4-hydroxyl benezophenone (4HB) with free available chlorine (FAC) was characterized. Eight major products were detected and seven of them were identified. Transformation pathways of 4HB under acid, neutral, and alkaline conditions were proposed respectively. The transformation mechanisms involved electrophilic chlorine substitution of 4HB, Baeyer-Villiger oxidation of ketones, hydrolysis of esters and oxidative breakage of benzene ring. The orthogonal experiments of pH and dosages of disinfectant chlorine were conducted. The results suggested that pH conditions determined the occurrence of reaction types, and the dosages of disinfectant chlorine affected the extent of reactions. Photobacterium assay demonstrated that acute toxicity had significant increase after chlorination disinfection of 4HB. It was proved that 3, 5-dichloro-4HB, one of the major transformation products, was responsible for the increasing acute toxicity after chlorination. It is notable that, 4HB at low level in real ambient water matrices could be transformed during simulated chlorination disinfection practice. Especially, two major products 3-chloro-4HB and 3, 5-dichloro-4HB were detected out, implying the potential ecological risk after chlorination disinfection of 4HB. Highlights: 7 transformation products in 4HB chlorination disinfection system were identified. Transformation pathways of 4HB during chlorination disinfection were proposed. Acute toxicity increased after chlorination due to the formation of 3, 5-dichloro-4HB. The transformation mechanisms of 4HB can be repeated in ambient water matrices.